2011
DOI: 10.1016/j.adolescence.2011.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Selective neurocognitive impairments in adolescents with major depressive disorder

Abstract: This study investigated whether major depression in adolescence is characterized by neurocognitive deficits in attention, affective decision making, and cognitive control of emotion processing. Neuropsychological tests including the Wechsler Abbreviated Scale of Intelligence, the Continuous Performance Test–Identical Pairs, the Attention Network Test, the Iowa Gambling Task, the Emotional Go-NoGo Task, and the Face Go-NoGo Task were administered to adolescents with Major Depressive Disorder (MDD) (n = 31) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
95
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(109 citation statements)
references
References 51 publications
13
95
0
1
Order By: Relevance
“…In depression, there is also evidence for impaired performance on the Iowa Gambling Task (Must et al 2006(Must et al , 2013Cella et al 2010;Han et al 2012), though with some studies not finding impairment (Westheide et al 2007;Smoski et al 2008). There is also evidence of impairments in reversal learning in depression (Murphy et al 2003;Robinson et al 2012;Hall et al 2014).…”
Section: Depressionmentioning
confidence: 89%
“…In depression, there is also evidence for impaired performance on the Iowa Gambling Task (Must et al 2006(Must et al , 2013Cella et al 2010;Han et al 2012), though with some studies not finding impairment (Westheide et al 2007;Smoski et al 2008). There is also evidence of impairments in reversal learning in depression (Murphy et al 2003;Robinson et al 2012;Hall et al 2014).…”
Section: Depressionmentioning
confidence: 89%
“…On the other hand, Mayes et al [58] found no difference on the Gordon Diagnostic System [30] version of the CPT between healthy control participants and anxious/depressed children. Han and colleagues [34] employed a version that manipulated load thus adding a working memory component and found a difference but this disappeared when adjusting for IQ differences between the groups. Günther and colleagues found no evidence for a deficit in sustaining attention in children with depressive disorders in either their 2004 or in their 2011 study.…”
Section: Attentionmentioning
confidence: 97%
“…Six studies included in the review used different versions of the continuous performance test (CPT) to assess the ability to sustain attention in paediatric depression [11,13,15,34,54,58]. Two reported medium effect sizes for CPT omissions, commissions and greater inconsistencies in reaction times for the clinical group [13,15].…”
Section: Attentionmentioning
confidence: 98%
“…In young people, neurocognitive deficits in sustained attention and executive function including spatial working memory have been observed in depressive disorders (Castaneda et al, 2008;Han et al, 2012;Maalouf et al, 2011), substance abuse issues (Solowij et al, 2012;Tapert and Brown, 1999) and those at risk of psychosis (Myles-Worsley et al, 2007). There is a paucity of evidence investigating the impact of these neurocognitive deficits on employment and educational engagement, and to our knowledge there are no studies assessing neurocognitive impairments in mild or subthreshold disorders in a youth help-seeking population.…”
Section: Introductionmentioning
confidence: 94%
“…Reviews of cognitive impairments in depressive and anxiety disorders in young adults focus on major depressive disorder as there is a paucity of studies with dysthymia or minor depressive disorder (Castaneda et al, 2008), which would have provided a helpful comparison. However, executive function deficits, including attentional and working memory impairment, have been reported in young adults with major depression (Castaneda et al, 2008;Han et al, 2012) and in a non-diagnostic specific sample of young adults with a history of childhood abuse (Gould et al, 2012). Although the current study did not compare cognitive outcomes between abstinent participants and substance users, previous studies have reported greater reflection impulsivity and impaired decision making with the information sampling task amongst adults who are current and reformed (1-8 years) amphetamine and opiate drug users (Clark et al, 2006).…”
Section: Vocational Functioning Neurocognitive Outcomes and Associatmentioning
confidence: 99%